Disentangling the effects of trait and state worry on error‐related brain activity: Results from a randomized controlled trial using worry manipulations. (30th March 2022) - Härpfer, Kai; Carsten, Hannes Per; Löwisch, Kim; Westermann, Nele; Riesel, Anja
Abstract: Enhanced amplitudes of the error‐related negativity (ERN) have been suggested to be a transdiagnostic neural risk marker for internalizing psychopathology. Previous studies propose worry to be an underlying mechanism driving the association between enhanced ERN and anxiety. The present preregistered study focused on disentangling possible effects of trait and state worry on the ERN by utilizing a cross sectional observational and a longitudinal randomized controlled experimental design. To this end, we examined the ERN of n = 90 students during a flanker task (T0), which were then randomly assigned to one of three groups (worry induction, worry reduction, passive control group). Following the intervention, participants performed another flanker task (T1) to determine potential alterations of their ERN. Manipulation checks revealed that compared to the control group, state worry increased in the induction but also in the reduction group. ERN amplitudes did not vary as a function of state worry. An association of trait worry with larger ERN amplitudes was only observed in females. Furthermore, we found larger ERN amplitudes in participants with a current or lifetime diagnosis of internalizing disorders. In summary, our findings suggest that the ERN seems to be insensitive to variations in state worry, but that an elevated ERN is associated with the trait‐like tendency to worry and internalizing psychopathology, which is consistent with the notion that the ERN likely represents a trait‐like neural risk associated with anxiety. Abstract : There is an ongoing debate in the literature: whether the error‐related negativity (ERN) has trait‐like characteristics indicating risk for psychopathology or whether it is sensitive to state fluctuations such as symptom alterations. In a preregistered randomized controlled trial, participants were randomly assigned to three groups including a worry induction, worry reduction, and a passive control group. Our findings support the notion of the ERN as a trait‐like neural risk marker or endophenotype.